Visualization of biochemical activity of microorganisms genus Aerococcus species Aerococcus viridans - Kremenchutsky, G; Stepansky, D; Koshevaya, I; Turlun, S (Annals of Mechnikov's Institute, 2020)
Introduction.Aerococci are catalase-negative Gram-positive microorganisms, widespread in the environment, in the cold-blooded microbiocenoses [1, 2] and warm-blooded organisms [3]. Currently, there are seven species of the Aerococcus genus [4]. Type A. viridans got its name as a result of greening blood agar around the growing colonies. It was found that one of the products of A. viridans growth is hydrogen peroxide, has an antagonistic effect on various kinds of bacteria "in vitro" and "in vivo" [5]. It was subsequently found thathydrogen peroxide and superoxide radical are produced as a result of NAD-independent lactatoxidase [6,7] and piruvatoxidase functioning[8]. The oxidative ability of A. viridans is a distinctive feature and allows to visualize these properties using a specific indicator medium [9]. We have developed an indicator that enables to visualize oxidation and reduction properties of aerococci. Material & methods. Auto-symbiotic cultures of A.viridans was used for studying of oxidase-reductase activity, inoculated from human body, an industrial strain of A.viridans 167, used for the preparation of "A-bacterin", culture of Aureobasidium pullulans B5, isolated from the soil and having glucose oxidase activity [10]. Designed indicating medium were also tested in the inoculation of aerococci crops, having lactatoxidase activity of biomaterials from birds and mammals.As a basis for the indicating media (IM) IM1 media was selected with following composition (g per 1 liter of water)Iodide / potassium 26.0Soluble starch 10.0Nutrient agar 30.0For visualization of oxidase-reductase activity of aerococci acellular components IM4 was developed based on IM3, in which distilled water after double purification was used instead of tap water and highly purified agar-agar was used instead of standard nutrient agar. Results & discussion. IM1 is used to test the oxidative properties of aerococci crops. IM manifests the appearance of a dark purple color, after processing the surface of cups with 10% sulfuric acid. Dark purple areas with lactatoxidase activity in the growth zone of the culture are clearly visible. IM2 with high content of KJ can be used for isolation of aerococci colonies from contaminated biological material.IM3 with sodium selenite at a concentration of 1 g / l was used to visualize the reductase activity of microorganisms. Selenium recovered with the advent of the red color in the areas of crop growth and the colonies while growth of aerococcuses.Nutrient indicator medium IM3, containing an increased concentration of KJ, can be used for isolation and studying the oxidizing ability of different microorganisms which produce hydrogen peroxide in the oxidation of biological substrates.IM4 allows us to study the biochemical activity of the enzyme complex (EC) obtained by ultrasound (US) from washed thoroughly biomass of aerococcuses [11] and biological substrates.Conclusion.1. Indicator nutrient mediums IM1, IM2, containing the KJ and soluble starch allows to visualize the oxidizing power of aerococci and isolate them together with another microorganisms from contaminated biological products (water, air, soil, biological fluids).2. The indicator nutrient media IM3 allows (simultaneously with oxidase activity of microorganism) to visualize reductase activity in the reduction of selenium with classification on biological types.3. Minimal (hungry) IM4 allows us to observe the interaction between aerococci enzyme complex and substrates of oxidation and reduction, with further extrapolation of the results to the role of aerococci in microbiotope of host organism.The proposed indicator media can be used for microbiological and genetic studies, microbiological determination of amino acids, vitamins and nitrogenous bases.